Advanced dynamics - Greenwood, Donald T. (Cambridge University Press, 2003)
Advanced Dynamics is a broad and detailed description of the analytical tools of dynamics. The strengths and weaknesses of various approaches are discussed, and particular emphasis is placed on learning through problem solving. Many worked examples and homework problems are provided.